Living apart together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Beyond inequalities. Women in Angola By Naiole Cohen dos Santos, Southern African Resource and Documentation Centre, 2000. 138 pp. ISBN 0797417508 US$ 13.75 Euro 15.20